How to Befriend a Cadaver - Hulbert, Maggie (Ars Medica, 2018)
First, remove the skin. It’s easiest to pull it off in strips, peeling off layers of hair and fat like peeling an orange. It will be simultaneously gruesome and tedious. Your hands will cramp and your mouth will taste like disinfectant, but show no weakness. Your cadaver is testing you, waiting for you to succumb to the fragility of being alive and having senses. Go home that night and have a shower, but know the smell will not leave you for four months. This cadaver is yours for the term: Male, aged 57.